Quantitative Imaging of Rapidly Decaying Evanescent Fields Using Plasmonic Near-Field Scanning Optical Microscopy - Zhang, Zhen (Nature Publishing Group, 2013)
Non-propagating evanescent fields play an important role in the development of nano-photonic devices. While detecting the evanescent fields in far-field can be accomplished by coupling it to the propagating waves, in practice they are measured in the presence of unwanted propagating background components. It leads to a poor signal-to-noise ratio and thus to errors in quantitative analysis of the local evanescent fields. Here we report on a plasmonic near-field scanning optical microscopy (p-NSOM) technique that incorporates a nanofocusing probe for adiabatic focusing of propagating surface plasmon polaritons at the probe apex, and for enhanced coupling of evanescent waves to the far-field. In addition, a harmonic demodulation technique is employed to suppress the contribution of the background. Our experimental results show strong evidence of background free near-field imaging using the new p-NSOM technique. Furthermore, we present measurements of surface plasmon cavity modes, and quantify their contributing sources using an analytical model.